Water-blocking Asphyxia of N95 Medical Respirator During Hot Environment Work Tasks With Whole-body Enclosed Anti-bioaerosol Suit - Jintuo Zhu; Qijun Jiang; Yuxuan Ye; Xinjian He; Jiang Shao; Xinyu Li; Xijie Zhao; Huan Xu; Qi Hu (Elsevier, 2023)
Background: During hot environment work tasks with whole-body enclosed anti-bioaerosol suit, the combined effect of heavy sweating and exhaled hot humid air may cause the N95 medical respirator to saturate with water/sweat (i.e., water-blocking). Methods: 32 young male subjects with different body mass indexes (BMI) in whole-body protection (N95 medical respirator + one-piece protective suit + head covering + protective face screen + gloves + shoe covers) were asked to simulate waste collecting from each isolated room in a seven-story building at 27-28°C, and the weight, inhalation resistance (Rf), and aerosol penetration of the respirator before worn and after water-blocking were analyzed. Results: All subjects reported water-blocking asphyxia of the N95 respirators within 36-67 min of the task. When water-blocking occurred, the Rf and 10-200 nm total aerosol penetration (Pt) of the respirators reached up to 1270-1810 Pa and 17.3-23.3%, respectively, which were 10 and 8 times of that before wearing. The most penetration particle size of the respirators increased from 49-65 nm before worn to 115-154 nm under water-blocking condition, and the corresponding maximum size-dependent aerosol penetration increased from 2.5-3.5% to 20-27%. With the increase of BMI, the water-blocking occurrence time firstly increased then reduced, while the Rf, Pt, and absorbed water all increased significantly. Conclusions: This study reveals respirator water-blocking and its serious negative impacts on respiratory protection. When performing moderate-to-high-load tasks with whole-body protection in a hot environment, it is recommended that respirator be replaced with a new one at least every hour to avoid water-blocking asphyxia.